Left Amyand’s hernia with inflamed appendix and sealed of perforated caecum an unusual case - Mohite, Reshma Bhalchandra; Iyer, Vishaka; Beedkar, Anant N.; Jadhav, Sarojini (International Surgery Journal, 2021)
Amyand’s hernia is defined as the hernia with appendix normal, inflamed or perforated as content. 1% of inguinal hernias are Amyand’s and amongst them 0.1% contains inflamed appendix. Commonly encountered on right size due to anatomical position of appendix. Left Amyand’s is rare and associated with intestinal malrotation, situs invertus and mobile caecum. Here, we presented an interesting case of left irreducible hernia in 70 years old gentleman with no signs of acute obstruction or strangulation, patient underwent emergency laparotomy in which hernial sac contents were inflamed ileal loop, inflamed appendix and perforated caecum in 70 years old man is rare presentation and not reported in any literature as per our knowledge. Resection of inflamed bowel loop with ceacum done along with ileo ascending anastomosis with primary tissue repair done. Post-operative period was uneventful. Hernia sac contents are most of the time surprising and their management sometimes differ according to the content. Appendix in hernia sac is found in 1% of all hernia but lack of facility for the pre-operative diagnosis and varied presentation it is challenging to diagnose and operate accordingly.